제8차 CNI 환경브라운백 세미나(김중기) - 김중기,정종관,백송이,차정우,고명찬,강건,명형남,정옥식,천서이,사공정희 (충남연구원, 2015)
Integrated Valuation of Ecosystem Services and Tradeoffs:Use an ecosystem service modeling approach to inform decisions for sustainable development Choong-KiKim Korea Environment Institute (KEI) (ckkim@kei.re.kr) - 이후 생략